Study of the Predictive Validity of the Burnout Granada Questionnaire in Police Officers - De La Fuente-Solana, Emilia I.; Ortega-Campos, Elena; Vargas-Román, Keyla; Cañadas-de la Fuente, Guillermo Arturo; Ariza, Tania; Aguayo-Estremera, Raimundo; Albendín-García, Luis (International Journal of Environmental Research and Public Health, 2021)
Professionals with burnout have negative physical and psychological effects, with adverse consequences in their workplace. Burnout mainly affects assisting professions; amongst them, police work is one of the professions at risk of suffering from this syndrome. The aim of this research is to study the adequacy of the Maslach Burnout Inventory and Granada Burnout Questionnaire instruments to measure burnout in police officers through the study of the reliability and validity (concurrent and predictive) of these instruments. A cross-sectional study was carried out. The sample was composed of 1884 police officers, mostly men (85.4%), with an average age of 35.04 (SD = 8.30). The Maslach Burnout Inventory and Granada Burnout Questionnaire were used to measure burnout. The results obtained in this study support the adequacy of both instruments for measuring burnout. The correlation coefficients between the dimensions are significant, with a medium-high magnitude. Participants with burnout had significantly higher scores in emotional exhaustion and depersonalization and lower scores in personal accomplishment in both instruments. The area under the curve estimated for the Granada Burnout Questionnaire provided evidence of the predictive validity of the instrument. The police profession needs validated and sensitive tools to identify police changes in the dimensions of burnout. The Granada Burnout Questionnaire instrument correctly classifies burnout in police professionals.
Keywords: burnout; GBQ; MBI; police officers; validity; JCR; Scopus